2021
DOI: 10.1002/jqs.3280
|View full text |Cite
|
Sign up to set email alerts
|

A dated volcano‐tectonic deformation event in Jan Mayen causing landlocking of Arctic charr

Abstract: We provide the first documentation of tectonic deformation resulting from a volcanic eruption on the island of Jan Mayen. Vertical displacement of about 14 m southwest of the stratovolcano Beerenberg is associated with an eruption in AD 1732 on its southeastern flank. The age of the uplift event is bracketed by radiocarbon-dated driftwood buried by material deposited due to uplift, and by tephra from this eruption. Constraints, inferred from radiocarbon ages alone, allow for the possibility that uplift was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…1). According to Kandilarov et al (2012) and Larsen et al (2021), the Jan Mayen microcontinent (JMMC, Fig. 2a) is a structural entity enclosing the Jan Mayen Ridge (JMR) and the surrounding area, including the Jan Mayen Basin (JMB), the Jan Mayen Basin South (JMBS), the Jan Mayen Trough (JMT), and the Southern Ridge Complex (SRC) (see Fig.…”
Section: Jan Mayen Volcanismmentioning
confidence: 99%
“…1). According to Kandilarov et al (2012) and Larsen et al (2021), the Jan Mayen microcontinent (JMMC, Fig. 2a) is a structural entity enclosing the Jan Mayen Ridge (JMR) and the surrounding area, including the Jan Mayen Basin (JMB), the Jan Mayen Basin South (JMBS), the Jan Mayen Trough (JMT), and the Southern Ridge Complex (SRC) (see Fig.…”
Section: Jan Mayen Volcanismmentioning
confidence: 99%
“…Isostatic changes will also have some influence on the calculated exposure ages as they may change the elevation of a sample. A recent study by Larsen et al (2021) [2] identified a 14 m vertical tectonic displacement of southwest Beerenberg, following an eruption in 1732. So far, this is the only documented postglacial displacement, but we cannot exclude that there have been other instances of vertical displacements on the island due to both glacioisostasy and volcanic activity.…”
Section: Evaluation Of General Uncertaintiesmentioning
confidence: 99%
“…Its isolated position 550 km north of Iceland and 450 km east of Greenland in the Norwegian-Greenland Sea (Figure 1) makes it an interesting location for investigations of the climate history in the North Atlantic. A research campaign to reconstruct the glaciation and climate history of the island was therefore started in 2014 [1,2]. As part of that campaign, 89 samples for cosmogenic nuclide exposure age dating ( 36 Cl) were collected with the aim of dating glacial and volcanic events on the island.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation